A LITERATURE REVIEW ON DIMENSIONS OF BRAND EQUITY IN THE INSURANCE INDUSTRY OF SAUDI ARABIA - Hassan, Masood; Hassan, Mehboob-ul; Imam Uddin (Jurnal Syariah, 2022)
Branding is generally regarded as a unique approach for brand equity that enhances the corporate reputation of stakeholders. Insurance firms acknowledge and handle goods in a changing business environment as important assets. Brand is a system with multi-dimensional principles that satisfy consumers’ wants, expectations and needs, including practical and emotional elements. One of the branding goals is to distinguish the brand from its unique and valued characteristics. If the brand is an important element in every marketing effort, it must be recognized that its equity definition is appropriate. Insurance companies attempt to maintain brand resources and other methods by means of suitable brand distinctiveness. This paper attempts to describe the aspects of specialized literature. Since Saudi insurance is such a recent phenomenon, it has not undergone a critical analysis of whether it fulfils the requirements for takaful insurance or not.